1972
DOI: 10.1042/bj1270669
|View full text |Cite
|
Sign up to set email alerts
|

The quantitative determination of phenylalanine hydroxylase in rat tissues. Its developmental formation in liver

Abstract: A sensitive method was developed for determining the phenylalanine hydroxylase activity of crude tissue preparations in the presence of optimum concentrations of the 6,7-dimethyl-5,6,7,8-tetrahydropterin cofactor (with ascorbate or dithiothreitol to maintain its reduced state) and substrate. Tissue distribution studies showed that, in addition to the liver, the kidney also contains significant phenylalanine hydroxylase activity, one-sixth (in rats) or half (in mice) as much per g as does the liver. The liver a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0

Year Published

1976
1976
1999
1999

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 19 publications
5
49
0
Order By: Relevance
“…was required to cause 85 % inhibition and that one-half of this dose resulted in only 35% inhibition. In adult livers with a higher basal phenylalanine hydroxylase activity (McGee et al, 1972a), the percentage inhibition caused by a maximally effective dose of pchlorophenylalanine was slightly higher than in immature rats (Table 1). (As shown by the values in line 3, a simultaneous administration ofphenylalanine did not influence the degree of inhibition.)…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…was required to cause 85 % inhibition and that one-half of this dose resulted in only 35% inhibition. In adult livers with a higher basal phenylalanine hydroxylase activity (McGee et al, 1972a), the percentage inhibition caused by a maximally effective dose of pchlorophenylalanine was slightly higher than in immature rats (Table 1). (As shown by the values in line 3, a simultaneous administration ofphenylalanine did not influence the degree of inhibition.)…”
Section: Resultsmentioning
confidence: 97%
“…Even the daily administration of phenylalanine plus p-chlorophenylalanine in the study of Andersen et al (1974) may have been insufficient, since a report by Lipton et al (1967) showed that, at least in adult p-chlorophenylalanine-treated rats, the concentrations of phenylalanine in plasma return to normal as early as 3 h after the administration of 12,umol of phenylalanine/lOg body wt. The extent of loss of phenylalanine hydroxylase activity was also uncertain, since the maximum effective dose of p-chlorophenylalanine in suckling rats has not been determined, nor was it known whether this agent inhibited the appreciable activity present in kidney (McGee et al, 1972a).…”
mentioning
confidence: 99%
“…In rodents, PAH is present mainly in the liver but also is found in the kidneys; it is first expressed only after birth, and the gene is induced by glucocorticoids and cyclic AMP (cAMP) (26,27,34,44,45,51). The hormone inducibility, distribution in tissues, late expression, and negative regulation by TSE1 (21) permit grouping of the rodent PAH with the neonatal hormone-inducible tyrosine aminotransferase (TAT) and phosphoenolpyruvate carboxykinase (PEPCK) genes.…”
mentioning
confidence: 99%
“…The PAH gene codes for an amino-acid-catabolizing enzyme, which hydroxylates phenylalanine to tyrosine. Previous attempts to prematurely induce this gene expression by glucocorticoids in vivo in the rat fetal liver have failed [33], but succeeded in vitro, when the hormones were added to isolated fetal hepatocytes in culture [34]. The addition of glucocorticoids to such cultured hepatocytes markedly increased the PAH mRNA from barely detectable levels.…”
Section: Discussionmentioning
confidence: 99%